Contested Governance in Japan - Hook, Glenn D. (The University of Sheffield/Routledge Japanese Studies Series, 2005)
Contested Governance in Japan extends the analysis of governance in contemporary Japan by exploring both the sites and issues of governance above and below the state as well as within it. This volume discusses the contested nature of governance in Japan and the ways in which a range of actors are involved in different sites and issues of governance at home, in the region and the globe. It includes chapters on global governance, local policy-making, democracy, environmental governance, the Japanese financial system, corruption, the family and corporate governance.